Teacher Constraints in Preparing Lesson Plan through Google Classroom - Dian Yurista Ningsih; Dewa Komang Komang Tantra; Luh Gd Rahayu Budiarta (Universitas Pendidikan Ganesha, 2021)
Implementing an effective teaching and learning process with the integration of online learning platforms is important for teachers, to maximize the online learning process. The purpose of this study is to analyze the obstacles in compiling the integrated lesson plans for google classroom. This study uses a qualitative design as a research design. The research subject in this study was an English teacher. The instrument used in this is a questionnaire containing aspects such as learning, learning materials, learning activities, media and learning resources, and learning objectives. The results show that there are several dominant obstacles, including online learning media as an intermediary for students in collecting results, online learning media that are only used to collect assignments, teachers have difficulty assessing student work from these activities, online learning platforms that are only used for conveying the material, type and technique of the assessment cannot be assessed from the activity. Based on the results of the study, it can be said that teachers experience several dominant obstacles in preparing lesson plans so that they need to be resolved by teachers through mastering five aspects of lesson plan so that they can be adapted to dynamic teaching and learning situations.